Central scotoma following phacoemulsification surgery: A case report on retinal phototoxicity - Tahmina Nazari; Maarten B. Jalink (American Journal of Ophthalmology Case Reports)
Phacoemulsification cataract surgery is a widely adopted, however despite its routine application and favorable outcomes, it is not devoid of risks. Complications are rare, with an even more infrequent occurrence of retinal phototoxicity. This case report delves into an instance of retinal phototoxicity in a 59-year-old Caucasian male following an uneventful phacoemulsification and intraocular lens implantation. Postoperatively, he experienced a small, central scotoma. Imaging revealed a small disruption in the outer retinal layers (subfoveal). In three months’ time, his central scotoma disappeared and the imaging showed improvement with only a minor outer retinal irregularity being present. This paper presents the case and discusses the risk factors to develop phototoxicity after phacoemulsification.